Pattern of admission and outcome of neonates admitted to tertiary care neonatal ICU: Neonatal Admission Pattern in NICU and Outcome (Journal of Fatima Jinnah Medical University, 2020)
Background: In the last two decades, the neonatal mortality and morbidity profile has reportedly improved due to better critical care facilities worldwide and neonatal mortality fell by 49%. However, in Pakistan, neonatal morbidity and mortality is still a major health problem and recent estimates has reported -0.33% per annum in Pakistan. It is important that the changed picture of neonatal morbidity and mortality should be determined. This study aims to assess the pattern of admission and outcome of neonates admitted to tertiary care neonatal intensive care unit of a tertiary care hospital in Rawalpindi.Subjects and methods: A cross-sectional study was conducted at the Neonatal Unit of the Military Hospital, Rawalpindi from January till June 2018. All consecutive neonates admitted in neonatal unit irrespective of gender were enrolled. The outcome of the admission in terms of discharge, expired or Left against medical advice (LAMA) were noted along with the baseline characteristics like age, gender, weight, gestational age, mode and place of delivery of the neonates.Results: Of 1922 neonates admitted in the study period, male preponderance was observed (63.2%). Most common reason for admission in neonates was preterm (n=445, 23.2%), followed by neonatal sepsis (n=405, 21.1%), and transient tachypnea of newborn in 248 (12.9%). Preterm was the most common diagnosis in both males and females, i.e. 265 (22%) and 180 (25%) respectively. Mortality was observed in 266 (13.8%) neonates while LAMA in 10 (0.5%) neonates. A significant difference in outcome was found with the diagnosis of the neonates (p-value
Keywords: Outcome; Neonates; Intensive Care Unit; Indictation